The impact of large structural shocks onn economic relationships: Evidence from oil price shocks - George Kapetanios; Elias Tzavalis (Queen Mary University of London, Department of Economics, 2004)
This paper introduces a new model of structural breaks which assumes that structural breaks are driven by large economic shocks. The model specifies that both the timing and size of breaks are stochastic and it can be used to investigate the impact of large economic shocks on the stability of economic relationships. An application of the model to the oil-macroeconomy relationship has shown that the apparent instability of this relationship since the oil crisis in year 1973 can be attributed to large oil price shocks.
Keywords: C13; C22; E32; 330; Structural breaks; State space model; Oil shocks; Mineral\~AƒÂlpreisschock; Strukturbruch; Sch\~AƒÂtzung; Welt; Makro\~AƒÂkonomischer Einfluss; Zustandsraummodell